Regulation of Antigen Export to the Cytosol During Cross-Presentation - Gros, Marine; Amigorena, Sebastian (Frontiers in Immunology, 2019)
Cross-priming refers to the induction of primary cytotoxic CD8+ T cell responses to antigens that are not expressed in the antigen presenting cells (APCs) that induce the priming (i.e responses to tumor antigens or to antigens from viruses that do no infect APCs). Cross-presentation names the process allowing uptake of antigens, their processing into peptides, and the subsequent loading and presentation of these peptides by Major Histocompatibility Complex (MHC) class I molecules. Despite extensive research efforts to understand the intracellular pathways underlying antigen cross-presentation, certain critical steps remain elusive and controversial. Here we review recent advances and general considerations about cross-presentation, focusing on the mechanisms involved in antigen export to the cytosol, a crucial step of this pathway.